Nursing Interventions for the Prevention and Management of Non-Communicable Diseases in Rural Areas: A Scoping Review - Meistvin Welembuntu; Iswanto Gobel; Yanli Everson Tuwohingide (Indonesian Journal of Global Health Research, 2025)
Non-communicable diseases (NCDs) are the leading global health issue, with a steadily increasing prevalence and the highest mortality rates worldwide. Nurses play a crucial role within communities; evidence-based nursing interventions warrant further exploration. This study aimed to identify, classify, and synthesize nursing interventions and their outcomes in preventing and managing non-communicable diseases in rural communities. A scoping review was conducted of studies published between 2015 and 2025, using the PubMed, ProQuest, and EBSCOhost databases. A total of 4,170 records were identified and screened using relevant keywords and Boolean operators, and articles meeting the inclusion criteria were analysed using Rayyan AI. Fourteen studies were included in the final review. These studies were conducted in rural areas across 11 countries, including Australia, the USA, Portugal, Spain, China, Canada, Africa, Rwanda, Iran, the Netherlands, and Turkey. The research designs included four qualitative studies, one cohort study, two quasi-experimental studies, three Randomized Controlled Trials (RCTs), two descriptive studies, and one anthropological study. Both independent and collaborative nursing interventions have been shown to improve behaviour change, promote healthy lifestyles, and increase knowledge among patients and communities regarding NCDs. It is expected that the nursing profession and policymakers can implement these nursing interventions in populations living in rural or underserved areas with limited access to healthcare facilities.